New species and additional faunistic record of Taiwanocantharis Wittmer, 1984 from China (Coleoptera: Cantharidae) - Hua, Ruo-Bing; Liu, Hao-Yu; Yang, Xing-Ke; Yang, Yu-Xia (Zootaxa, 2026)
Taiwanocantharis shergaoensis (Wittmer, 1989) is recorded from China for the first time and redescribed herein. A new species of Taiwanocantharis is described from Xizang under the name of T. marginalis sp. nov. Both species are illustrated with habitus of both sexes, aedeagus, as well as female abdominal sternite VIII and reproductive systems.